2019
DOI: 10.15637/jlecon.6.018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship Between Inflation, Budget Deficit and Money Supply in Turkey by Ardl Approach 1980-2017

Abstract: Inflation is considered as a monetary phenomenon and its increase is linked with money supply according to the Monetarist view. In other words, the increase in budget deficits leads to an increase in money supply and as a result, inflation rates rise. Inflation is based on fiscal policies rather than monetary policies according to Price Level Fiscal Theory. Accordingly, increasing budget deficits leads to increases in loans, thus causes interest rates to rise and consequently inflation rises as money supply in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In other words, increasing budget deficits increases the inflation rate. The inference in question, as obtained from various country examples by Narayan et al (2006), Devapriya and Ichihashi (2012), Isaq and Mohsin (2015), Nguyen (2015), and Arjomand et al (2016), has been reached through studies conducted within the scope of Turkiye by Metin (1995Metin ( , 1998, Akçay et al (1996), Günaydın (2004), Oktayer (2010), Bayrak and Kanca (2013), Bedir and Tural (2014), İpek and Akar (2016), Öruç (2016), Alper (2018), Maraş andDumrul (2019), andErdil Şahin (2019). Contrary to the aforementioned studies, no study has been found that concludes that increasing the budget deficit reduces the inflation rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, increasing budget deficits increases the inflation rate. The inference in question, as obtained from various country examples by Narayan et al (2006), Devapriya and Ichihashi (2012), Isaq and Mohsin (2015), Nguyen (2015), and Arjomand et al (2016), has been reached through studies conducted within the scope of Turkiye by Metin (1995Metin ( , 1998, Akçay et al (1996), Günaydın (2004), Oktayer (2010), Bayrak and Kanca (2013), Bedir and Tural (2014), İpek and Akar (2016), Öruç (2016), Alper (2018), Maraş andDumrul (2019), andErdil Şahin (2019). Contrary to the aforementioned studies, no study has been found that concludes that increasing the budget deficit reduces the inflation rate.…”
Section: Literature Reviewmentioning
confidence: 99%